Comprometimento cidadão e inovações sociais: contribuições para o desenvolvimento urbano sustentável - Moschen, Suane de Atayde (My University, 2025)
The contemporary global landscape poses significant challenges to sustainable urban development. With more than half of the world's population living in urban areas - and projections indicating this figure may rise to 70% by 2050,the environmental and social impacts of urbanization are intensifying. On the other hand, isolated regulatory and technological measures have proven insufficient to address the complex environmental and social issues of urban contexts. The theme is complex because the city, understood as a social and spatial organization, combines collective, individual, and cultural dynamics that shape and sustain its local identity. In this context, citizen commitment becomes an essential factor, as it strengthens participatory processes, expands social mobilization capacity, and legitimizes public policies aimed at urban sustainability. Social innovation, in turn, emerges as a strategic element to foster structural change, mobilizing diverse actors around collective solutions. This research aimed to analyze how citizen commitment to social innovation initiatives contributes to sustainable urban development. A citizen science approach, combined with a mixed-methods design, was employed, structured in a sequential explanatory strategy that involved the active participation of Caxias do Sul inhabitants throughout all stages of the study. Data collection and analysis were organized into phases. In Phase 0, a systematic mapping of 56 social innovation initiatives was conducted, encompassing civil society organizations, collectives, social movements, startups, and university and business projects. In Phase 1, 446 responses were collected from a survey applied to citizens engaged in these initiatives, using an adapted scale of citizen commitment. In Phase 2, follow-up participants were selected for the qualitative stage of the study, which included focus groups that enabled a deeper understanding of motivations, perceptions, and obstacles to participation in social innovation for sustainable urban development. Finally, Phase 3 integrated the collected data, proposing a model that connects citizen commitment and social innovation as fundamental components in fostering sustainable urban development. The integration of quantitative and qualitative findings revealed a predominantly affective commitment profile in Caxias do Sul, with emphasis on belonging and personal meaning attributed to the city, low normative adherence, and an intermediate instrumental level. The mapping highlighted a plural ecosystem, intensive in networks and exchanges and characterized by diffuse community empowerment, though fragile in articulating sustainability challenges and measuring impact. The mixed-methods analysis supported the proposed theoretical model: citizen commitment to participation in social innovation to sustainable urban development, mediated by courses of action (planning, partnerships, and metrics) that channel affect into collective outcomes. Empirically, the findings provide insights into local governments, universities, and civil society in designing public policies and engagement practices, reinforcing strategies fostering belonging and collective identity are more effective than normative appeals or instrumental incentives. Furthermore, citizen science proved to be a promising method of knowledge co-production, enhancing social legitimacy and offering valuable inputs to monitor sustainability indicators and support the Sustainable Development Goals. [resumo fornecido pelo autor]
O cenário global contemporâneo impõe desafios significativos ao desenvolvimento urbano sustentável. Com mais da metade da população mundial vivendo em áreas urbanas e projeções que indicam a elevação desse índice para 70% até 2050, intensificam-se os impactos ambientais e sociais associados à urbanização. Por outro lado, medidas regulatórias e tecnológicas isoladas têm se mostrado insuficientes para enfrentar as complexas questões ambientais e sociais do meio urbano. O tema é complexo, pois a cidade, compreendida como uma organização social e espacial, combina dinâmicas coletivas, individuais e culturais que constroem e sustentam sua identidade local. Nesse contexto, o comprometimento cidadão torna-se um fator essencial, ao fortalecer processos participativos, ampliar a capacidade de mobilização social e legitimar as políticas públicas voltadas para a sustentabilidade urbana. A inovação social, por sua vez, surge como um elemento estratégico para promover mudanças estruturais, ao mobilizar atores diversos em torno de soluções coletivas. Esta pesquisa teve como objetivo analisar o comprometimento cidadão com iniciativas de inovação social para o desenvolvimento urbano sustentável. Foi empregada uma abordagem de ciência cidadã aliada a um método misto, estruturada em uma estratégia sequencial explanatória que combinou a participação ativa dos habitantes de Caxias do Sul em todas as etapas da pesquisa. A coleta e análise de dados foram organizadas em fases: na Fase 0, realizou-se o mapeamento sistemático de 56 iniciativas de inovação social, abrangendo organizações da sociedade civil, coletivos, movimentos sociais, startups, projetos universitários e empresariais. Na Fase 1, foram coletadas 446 respostas de uma survey aplicada a cidadãos engajados nessas iniciativas, utilizando uma escala adaptada de comprometimento cidadão. Na Fase 2 foram selecionados os participantes do follow-up para a etapa qualitativa do estudo. Ainda, foi composta por grupos focais, o que permitiu aprofundar a compreensão das motivações, percepções e obstáculos enfrentados na participação em inovações sociais para o desenvolvimento urbano sustentável. Por fim, a Fase 3 integrou os dados coletados, propondo um modelo que conecta o comprometimento cidadão e a inovação social como componentes fundamentais para promover o desenvolvimento urbano sustentável. A integração dos achados quantitativos e qualitativos revelou um perfil de comprometimento predominantemente afetivo em Caxias do Sul, com destaque para o pertencimento e o significado pessoal atribuídos à cidade, baixa adesão normativa e nível intermediário instrumental. O mapeamento mostrou um ecossistema plural, intensivo em redes e trocas e com empoderamento comunitário difuso, porém com fragilidades na explicitação de desafios de sustentabilidade e na mensuração de impacto. A análise mista sustentou o modelo teórico proposto: comprometimento cidadão - participação em inovação social - desenvolvimento urbano sustentável, mediado por cursos de ação (planejamento, parcerias e métricas) que canalizam o afeto em resultados coletivos. Empiricamente, os achados oferecem subsídios para governos locais, universidades e sociedade civil na formulação de políticas públicas e práticas de engajamento, reforçando que estratégias de fortalecimento do pertencimento e da identidade coletiva são mais eficazes do que apelos normativos ou incentivos instrumentais. Além disso, a ciência cidadã mostrou-se método promissor de coprodução de conhecimento, ampliando legitimidade social e oferecendo insumos para monitorar indicadores de sustentabilidade e apoiar os Objetivos de Desenvolvimento Sustentável. [resumo fornecido pelo autor]
Keywords: Desenvolvimento urbano sustentável; Inovações - Aspectos sociais; Comprometimento organizacional; Cidadania; Sustainable urban development; Inovation - Social aspects; Organizational commitment; Citizenship